Molecular magnetic resonance imaging discloses endothelial activation after transient ischaemic attack. (8th November 2016) - Quenault, Aurélien; Martinez de Lizarrondo, Sara; Etard, Olivier; Gauberti, Maxime; Orset, Cyrille; Haelewyn, Benoît; Segal, Helen C.; Rothwell, Peter M.; Vivien, Denis; Touzé, Emmanuel; Ali, Carine
Abstract : See Sun et al. (doi:10.1093/aww306 ) for a scientific commentary on this article . transient ischaemic attack (TIA) is a warning sign of increased stroke risk, but is difficult to diagnose. Quenault et al . report the preclinical development of a sensitive and non-invasive imaging method that detects subtle endothelial changes after TIA, when conventional MRI fails to detect any lesion. Abstract : Abstract : See Sun et al. (doi:10.1093/aww306 ) for a scientific commentary on this article . About 20% of patients with ischaemic stroke have a preceding transient ischaemic attack, which is clinically defined as focal neurological symptoms of ischaemic origin resolving spontaneously. Failure to diagnose transient ischaemic attack is a wasted opportunity to prevent recurrent disabling stroke. Unfortunately, diagnosis can be difficult, due to numerous mimics, and to the absence of a specific test. New diagnostic tools are thus needed, in particular for radiologically silent cases, which correspond to the recommended tissue-based definition of transient ischaemic attack. As endothelial activation is a hallmark of cerebrovascular events, we postulated that this may also be true for transient ischaemic attack, and that it would be clinically relevant to develop non-invasive in vivo imaging to detect this endothelial activation. Using transcriptional and immunohistological analyses for adhesion molecules in a mouse model, we identified brain endothelial P-selectin as a potential biomarker for transient ischaemic attack. We thus developed ultra-sensitive molecular magnetic resonance imaging using antibody-based microparticles of iron oxide targeting P-selectin. This highly sensitive imaging strategy unmasked activated endothelial cells after experimental transient ischaemic attack and allowed discriminating transient ischaemic attack from epilepsy and migraine, two important transient ischaemic attack mimics. We provide preclinical evidence that combining conventional magnetic resonance imaging with molecular magnetic resonance imaging targeting P-selectin might aid in the diagnosis of transient ischaemic attack.